A.M - G.M equality. :D

Algebra Level 3

Solve for a,b,c . :D

a=b = 4/3 . c=3/4 a=b=c= 3/4 a=c = 3/4 , c = 4/3 a=b=c= 4/3

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Jared Low
Dec 28, 2014

From AM-GM inequality, we have a b + b a 2 \frac{a}{b}+\frac{b}{a} \geq2 and analogously b c + c b 2 \frac{b}{c}+\frac{c}{b} \geq2 , c a + a c 2 \frac{c}{a}+\frac{a}{c} \geq2 . Summing up these inequalities nets us: a b + b a + b c + c b + c a + a c 6 \frac{a}{b}+\frac{b}{a}+\frac{b}{c}+\frac{c}{b} +\frac{c}{a}+\frac{a}{c} \geq6 , which has equality only at a b = b a , b c = c b , c a = a c \frac{a}{b}=\frac{b}{a}, \frac{b}{c}=\frac{c}{b}, \frac{c}{a}=\frac{a}{c} or equivalently a 2 = b 2 = c 2 a^2=b^2=c^2 , further simplifying to a = b = c a=b=c since we have a , b , c R + a,b,c \in \mathbb{R}^+ . SInce our given conditions have this equality, this means we indeed have a = b = c a=b=c for these set of equations.

Substituting a = b = c a=b=c into the second equation nets us 3 a a 2 = 3 a = 4 3*\frac{a}{a^2}=\frac{3}{a}=4 and consequently a = b = c = 3 4 \boxed{a=b=c=\frac{3}{4}}

Christian Daang
Oct 19, 2014

In Eqn 1, A.M - G.M Inequality.

a/b = b/a, b/c = c/b, c/a = a/c

=> a = b = c. Putting it in second eqn, we get 3/a = 4 => a = 3/4 = b = c

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...